2005
DOI: 10.1007/s11148-006-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Part 3. Phase Transformations within the Layer of a Dry Barrier Mixture for Aluminum Electrolysis Cells

Abstract: It has been established that transformations within the layer of a dry barrier mixture (DBM) are selective in character and are mainly confined to the upper zones of the innermost part (core) of DBM. The DBM layer undergoes a solid-liquid sintering in these zones. The glass phase thus formed prevents the electrolysis products from penetration into the DBM layer. Modifier admixtures -titanium and iron oxides, products of electrolysis and degradation of the refractory layer AlF, SiF 4 , and sodium oxide -decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…This is believed to be due to the formation of AlX 3 and AlOX, where X is a halogen (Swihart & Catoire, 2000). Another occurrence of aluminium oxyhalides is the cathode surface in the aluminium electrolysis cell (Sharapova et al, 2005). Petrographic analysis of cell materials has revealed oxyfluoride glasses with variable compositions of AlOF 1Àx and with index of refraction n = 1.33-1.362.…”
Section: Commentmentioning
confidence: 99%
“…This is believed to be due to the formation of AlX 3 and AlOX, where X is a halogen (Swihart & Catoire, 2000). Another occurrence of aluminium oxyhalides is the cathode surface in the aluminium electrolysis cell (Sharapova et al, 2005). Petrographic analysis of cell materials has revealed oxyfluoride glasses with variable compositions of AlOF 1Àx and with index of refraction n = 1.33-1.362.…”
Section: Commentmentioning
confidence: 99%
“…Considering this and the results of studying samples (28-1v) SBS [4] and also the situation that for the comparatively thin (up to 0.7 cm) working zone of refractory ShPD M -45 it should be least changed, containing elemental fluorine and sodium in the form of traces, and there is no silicon entrained in it, and long-prismatic titanium-containing mullite without changes, it may be concluded that it is a titanium-containing glass phase [15] alongside a glass phase of albite composition that fufils a protective function and prevents the refractory cathode lining from further breakdown. Sodium vapor and gaseous fluorine compounds AlF, NaAlF 4 , CaF, MgF, i.e.…”
mentioning
confidence: 89%
“…In the nepheline-glass matrix there is clearly recorded a-corundum, tetragonal titanium oxyfluoride TiOF, titanium oxyfluoride of nonstoichiometric composition (TONC), titanium fluoride of nonstoichiometric composition (TFNC). Results of x-ray structural studies of the working glassy zone of refractory ShPD M -45 after service are provided below 4 In comparing the characteristics of x-ray patterns for the test titanium fluorides and oxyfluorides with x-ray patterns of standard TiF 3 and TiOF, disturbance of the crystal lattice spacing is observed for titanium fluoride TiF 3 and titanium oxyfluoride TiOF of stoichiometric composition. This makes it possible to refer the test titanium fluorides titanium subfluoride, and titanium oxyfluoride to oxyfluoride of nonstoichiometric composition.…”
mentioning
confidence: 99%
“…During the combustion, one of the molecules formed is AlOCl [1]. Another occurrence of aluminum oxyhalides is on the cathode surface in the aluminum electrolysis cell [2]. Recent studies have shown AlOCl to be useful as a coagulating agent for cleaning wastewater from organic impurities [3].…”
Section: Introductionmentioning
confidence: 99%